COMPARISON OF THE CHRONIC KIDNEY DISEASE PROGRESSION IN TYPE 2 DIABETES BETWEEN DIABETES CLINIC AND INTERNAL MEDICINE CLINIC - Inkhong, Siwakorn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION There was no study to compare the rate of chronic kidney disease progression among patients with diabetes consulting in diabetes and internal medicine clinics. The present study aimed to compare the rate of renal progression and the risk factors for chronic kidney disease among patients in the diabetes and internal medicine clinics to improve the management and delay progression of renal impairment. METHODOLOGY Data were collected in Rajavithi Hospital from January 1, 2017 to January 30, 2021 in the retrospective cohort study. The inclusion criteria were patients with type 2 diabetes mellitus and CKD stage 3a or 3b in diabetes and internal medicine clinics. Baseline characteristics included age, sex, body weight, body mass index, comorbidities, blood chemistries composed of estimated glomerular filtration rate (eGFR), microalbuminuria, low-density lipoprotein (LDL), fasting blood sugar (FBS) and hemoglobin A1c (HbA1c) as well as medication prescription comprising of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs), sodium-glucose cotransporter type 2 (SGLT2) inhibitor, glucagon-like peptide-1 receptor agonist (GLP-1 RA) and statins. In addition, data from nephrology consultations were also collected. The primary outcomes were GFR change and CKD stage progression after two years of follow-up. RESULTS The number of patients who had CKD stage progression for two years who were treated in a diabetes clinic was significantly lower than those treated in an internal medicine clinic (37.1% [n = 124] vs. 52.7% [n = 184], p <0.001) and the mean GFR change after two years was significantly different (-6.30 ± 4.21 vs. -8.51 ± 5.14, p <0.001). After adjusting for covariates in repeated measurement analysis, it was found that the GFR decline and CKD stage progression was slower in patients treated in the diabetes clinic than in those treated in the internal medicine clinic but the difference was not statistically significant. Patients using ACEIs or ARBs, statin, SGLT2 inhibitors, and GLP-1RA and seeing nephrologists were significantly higher in the diabetes clinic than internal medicine clinic. CONCLUSION No significant difference was observed in the change of GFR or CKD stage progression between patients treated in the diabetes clinic and those treated in the internal medicine clinic, during the two-year follow-up period of our study. Further studies with longer follow-up periods are needed to investigate the long-term treatment outcomes for renal impairment in these patient populations.